Generalized Lagrangians and Spinning Particles - Rivas, M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We show that the spin structure of elementary particles can be naturally described by the generalized Ostrogradskii Lagrangians depending on higher-order derivatives. One component of a spin is related to the rotation of a particle and the other one, caused by the dependence of a Lagrangian on the acceleration, is known as a zitterbewegung component of spin.